2021
DOI: 10.1097/md.0000000000023627
|View full text |Cite
|
Sign up to set email alerts
|

Ursodeoxycholic acid improves pregnancy outcome in patients with intrahepatic cholestasis during pregnancy

Abstract: Background: Intrahepatic cholestasis of pregnancy (ICP) is a common complication in the third trimester of pregnancy, which may result in premature delivery, fetal distress, stillbirth, and other adverse pregnancy outcomes. Ursodeoxycholic acid (UDCA) is a first-line treatment for ICP and has been controversial in improving adverse pregnancy outcomes. The purpose of this protocol is to systematically evaluate the effect of UDCA on pregnancy outcomes in patients with intrahepatic cholestasis during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“… 21 , 36 , 42 The accumulation of cholic acid due to insufficient enzyme activity has been implicated in the progression of numerous diseases. 26 , 43 Furthermore, our research, along with others, has demonstrated that probiotic supplementation can enhance the activity of 7α-dehydrogenase, 21 , 43 , 44 thereby mitigating the impact of disease conditions by bolstering bile acid metabolism. In clinical settings, especially in pediatrics, such as children with CCHD, continuous oral probiotic supplementation is often recommended to restore a well-balanced intestinal microbiota.…”
Section: Discussionmentioning
confidence: 99%
“… 21 , 36 , 42 The accumulation of cholic acid due to insufficient enzyme activity has been implicated in the progression of numerous diseases. 26 , 43 Furthermore, our research, along with others, has demonstrated that probiotic supplementation can enhance the activity of 7α-dehydrogenase, 21 , 43 , 44 thereby mitigating the impact of disease conditions by bolstering bile acid metabolism. In clinical settings, especially in pediatrics, such as children with CCHD, continuous oral probiotic supplementation is often recommended to restore a well-balanced intestinal microbiota.…”
Section: Discussionmentioning
confidence: 99%